2012
DOI: 10.1038/ng.2445
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association meta-analysis identifies new endometriosis risk loci

Abstract: We conducted a genome-wide association (GWA) meta-analysis of 4,604 endometriosis cases and 9,393 controls of Japanese1 and European2 ancestry. We show that rs12700667 on chromosome 7p15.2, previously found in Europeans, replicates in Japanese (P = 3.6 × 10−3), and confirm association of rs7521902 on 1p36.12 near WNT4. In addition, we establish association of rs13394619 in GREB1 on 2p25.1 and identify a novel locus on 12q22 near VEZT (rs10859871). Excluding European cases with minimal or unknown severity, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
240
4
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 267 publications
(266 citation statements)
references
References 33 publications
8
240
4
11
Order By: Relevance
“…Our results are in agreement with previous studies that demonstrated an association between 1p36.33 and endometriosis [34][35][36]. This locus contains markers located in or near the WNT4 gene, which plays an important role on the development of the female reproductive tract and steroidogenesis [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with previous studies that demonstrated an association between 1p36.33 and endometriosis [34][35][36]. This locus contains markers located in or near the WNT4 gene, which plays an important role on the development of the female reproductive tract and steroidogenesis [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…29,30 Substantial progress has been made in the discovery of genomic regions contributing to endometriosis risk. New genome-wide association (GWA) studies, 31 replication studies, 32,33 and meta-analyses 30,34 show remarkable consistency in the size and direction of effect for risk variants across studies and across ethnic groups. There are at least 6 genomic regions showing significant association with endometriosis of any disease stage.…”
Section: Genetics Epigenetics and Genomicsmentioning
confidence: 99%
“…The genetic factors may increase one's predisposition to endometriosis. It is suggested that genetic factors which are responsible for the etiopathogenesis of the endometriosis are multifactorial and polygenic 10 . The genetic predisposition probably increases the tendency of recurrence of endometriosis lesions with the above mechanisms.…”
Section: Discussionmentioning
confidence: 99%